Precision Probing of O-GalNAc Glycosylation Using Bump-and-Hole Engineering - Abdul Zafar; Benjamin Schumann (CHIMIA)
Glycosylation is a profound influencer of glycoprotein function. Glycans have a critical impact on health and disease, yet the tools to study them have trailed behind proteins and nucleic acids. O-GalNAc glycosylation involves the addition of N-acetylgalactosamine (GalNAc) to protein substrates. Dysregulation of O-GalNAc glycosylation is implicated in many pathologies such as cancer. Studying O-GalNAc glycosylation is complicated by the lack of a consensus sequence for initiation and the complex interdependence between a large family of 20 GalNAc transferases (GalNAc-Ts) in human cells. These issues necessitate precise methods of interrogating enzyme function. Herein, we discuss our own advances into the generation of precision tools to study O-GalNAc glycosylation and other glycosylation types. We discuss the use of bump-and-hole engineering to illuminate the roles of individual GalNAc-Ts. Engineering biosynthetic pathways enables cell line-specific uptake of chemical, editable sugars in co-culture settings. We provide an insight into the state-of-the-art in this field.